2020
DOI: 10.1002/pca.3019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of kavalactones in kava dry extracts: comparison of multi‐standards and single standard validation approaches

Abstract: Introduction Dried extracts of Piper methysticum G. Forst, also known as kava, has been widely used due to its anxiolytic and sedative properties. In order to assure the quality of these extracts, it is essential to accurately quantify kavalactones, known as the active principle. Objectives To develop and validate an analytical method for the simultaneous quantification of six major kavalactones (kavain, dihydrokavain, methysticin, dihydromethysticin, yangonin and demethoxyyangonin) in kava extracts, comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The content of KVN in the kava-kava capsules was 2.1 ± 0.1% (w/w), equivalent to 13.7 ± 0.3 mg/capsule. This value is in agreement with a previous study that found values between 1.2 to 5.2% (w/w) 25 . The quality control analysis of the P. methysticum capsules demonstrated the presence of other peaks in addition to KVN ( 3 ) ( Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The content of KVN in the kava-kava capsules was 2.1 ± 0.1% (w/w), equivalent to 13.7 ± 0.3 mg/capsule. This value is in agreement with a previous study that found values between 1.2 to 5.2% (w/w) 25 . The quality control analysis of the P. methysticum capsules demonstrated the presence of other peaks in addition to KVN ( 3 ) ( Fig.…”
Section: Resultssupporting
confidence: 94%
“…The content of KVN (the main chemical active constituent) was determined by HPLC as already described by our group [25]. Briefly, a stock solution of the KVN standard (1 mg/mL) was prepared in methanol.…”
Section: Phytomedicines and Quality Controlmentioning
confidence: 99%
“…In addition, these TC compounds were calculated using tinosporide as a single standard in the validated analytical method [32]. Supporting Information Table S4 showed that the content values (% relative error) differed from results obtained against external standard standards from 25.00% to 70.34% (Table S5) for 15 samples in a single standard approach due to contributing factors of variations in chemical classes and polarity of compounds.…”
Section: Application Of Hplc-pda Detector Methods Tc Extractmentioning
confidence: 99%
“…Further, each sample was analyzed in triplicate using an external standard, single standard (tinosporide), and optimized multi-class standards (cordifolioside A, magnoflorine, 20-β-hydroxy ecdysone, tinosporide) approach with the respective % coefficient of variations. The multi-class standards were selected per the representative chemical class of TC compounds [32]. These optimized four multi-class standards were selected from clerodane diterpene glycosides (cordifolioside A, syringin, tinosporaside), alkaloids (magnoflorine, jatrorrhizine, tetrahydropalmatine), clerodane furanoditerpenes (8-hydroxy tinosporide, tinosporide, columbin), and phytosterol class (20-β-hydroxy ecdysone).…”
Section: Application Of Single and Multi-class Standard Validated Qua...mentioning
confidence: 99%
“…Ultra-performance liquid chromatography high-resolution tandem mass spectrometry (UPLC–MS/MS) has also shown high selectivity and specificity, which can be useful to characterize kava products and to obtain more information on its pharmacokinetics data in animals and humans [ 33 ]. Finally, the usage of high-performance liquid chromatography interfaced to a diode array detector (HPLC–DAD) allowed the quantification of total kavalactone content and its distribution profile [ 34 ].…”
Section: Chemical Aspects Of Kavamentioning
confidence: 99%